Logística, risco e resiliência no setor de hortifruti em Santana do Livramento (RS) - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study aims to analyze the logistical challenges, risks, and resilience within the fresh produce (hortifruit) sector in the municipality of Sant’Ana do Livramento (RS), a region characterized by its distance from the state’s main supply center, CEASA/RS. The research was conducted through a multiple case study, involving one wholesale and one retail company, with data collected through semi-structured interviews, participant observation, and document analysis. The results show that the distance from CEASA, the poor condition of highways, and the lack of adequate infrastructure directly affect product quality, operational costs, and supply continuity. As a contribution, the study presents an action plan based on the 5W2H methodology, offering suggestions to improve logistics management and crisis response capacity. The research contributes to strengthening the regional fresh produce sector and highlights the importance of preventive and adaptive strategies in vulnerable contexts.
Logistics, risk, and resilience in the fresh produce sector in Santana do Livramento (RS)
Keywords: CEASA/RS; Logística; Hortifruti; Logistics; Fresh produce; CIENCIAS SOCIAIS APLICADAS